The Impact of Celebrity Endorsements Used in Television Advertisements on Children’s Pester Power in China - Li, Jia-Ying (2019)
Children nowadays are playing an increasingly important role in family purchase decision-making. Television advertising has been regarded as one of the most influential consumer socialisation agents which enable children to gain knowledge about consumption and a highly debated probable cause of parent-child conflict such as pester power. This study aims to determine in a Chinese context how children gain the power to influence family purchase decision making and how much impact TV advertising and celebrity-endorsed TV advertising act as factors have on children’s purchase intention and pestering behaviour.